Data and Error Analysis for an Undergraduate Experiment - Singh, Nimmi; Mamta,; Kumar, Kuldeep; Singh, Inderpreet; Arun, P. (European Journal of Applied Sciences, 2025)
Undergraduate students in the physics lab are expected to report their experimental results with possible errors or uncertainties, however, our experience at University of Delhi’s under-graduate level classes is that the students do not understand the significance of error analysis in an experiment and carry a lot of misconceptions. In an age, where, students are looking for quick solutions/ reads, the textbooks on error analysis and statistical mathematics seem to be too lengthy, abstract, theoretical and mundane. To address this problem, we decided to put together an article that is a short version of error analysis. The present work develops the standard ideas of error analysis around the data collected from a simple Ohm’s law experiment, an experiment done by almost all science students at school level.